2019
DOI: 10.13080/z-a.2019.106.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic seed treatment methods on spring barley seed quality, crop, productivity and disease incidence

Abstract: Low energy electrons (electron treatment), aerated steam (thermal treatment) and a bacterial product Cedomon containing Pseudomonas chlororaphis (bacterial treatment) were selected for the trial as the most popular seed treatment methods in Western and Northern Europe. This trial was aimed to evaluate the effect of treatments on seed sanitation, crop and disease development and yield parameters. Two spring barley (Hordeum vulgare L.) cultivars 'Luokė' and 'Alisa DS' were investigated during 2014-2015 under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In internal grain tissues of all tested barley genotypes, the prevailing fungus in the spectra was Bipolaris sorokiniana (teleomorph: Cochliobolus sativus) (Figure 4). This agrees with recent publications on fungal spectra in barley grains in the Baltic region [49,50]. B. sorokiniana causes severe diseases and significant yield losses mainly in warm humid growing regions; nevertheless, it has spread towards the Northern Hemisphere [6,51].…”
Section: Discussionsupporting
confidence: 92%
“…In internal grain tissues of all tested barley genotypes, the prevailing fungus in the spectra was Bipolaris sorokiniana (teleomorph: Cochliobolus sativus) (Figure 4). This agrees with recent publications on fungal spectra in barley grains in the Baltic region [49,50]. B. sorokiniana causes severe diseases and significant yield losses mainly in warm humid growing regions; nevertheless, it has spread towards the Northern Hemisphere [6,51].…”
Section: Discussionsupporting
confidence: 92%
“…The main effect of these methods is seed sanitation, while not affecting the growing part of plants after seed germination. Liatukas et al (2019) [87] reported that bacterial treatment with Cedomon increased the yield of two varieties of barley, Luok ė and Alisa DS, by an average of 3%. This treatment improved neither seed health nor crop stand density in the Luok ė variety; however, it had a positive effect on the seeds of Alisa DS in the experimental years 2014 and 2015.…”
Section: Disinfection Of Cereal Crops Using Hot Watermentioning
confidence: 99%
“…Field trials in Sweden (Johnsson et al, 1998), Finland (Lötjönen and Torniainen, 2005) and Lithuania (Liatukas et al, 2019) have revealed that P. chlororaphis MA 342 can effectively control seedborne cereal pathogens that are present on the seed or near the seed coat such as Pyrenophora spp., but does not control seedborne pathogens like the loose smut Ustilago nuda that are located in the seed embryo. There is no effect either against soilborne diseases or leaf diseases.…”
Section: Commercial Pseudomonas-based Bioprotectantsmentioning
confidence: 99%
“…Average yield increases in spring barley range between 2% and 5%, but there are strong differences between cultivars. In field trials in Lithuania, seeds of the cultivar 'Alisa DS' were effectively sanitized by the use of Cedomon, leading to yield increases of 5-15%, while this was not observed on the cultivar 'Luoke' (Liatukas et al, 2019). Field experiments in Finland have revealed that Cedomon could control net blotch (Pyrenophora tera) in barley nearly as well as chemical products and increased yield with 200-300 kg.…”
Section: Commercial Pseudomonas-based Bioprotectantsmentioning
confidence: 99%